Aplicabilidade da voltametria de pulso diferencial na quantificação de ácido fólico e ácido oxálico: um método comparativo - Araujo, Eliane Gonçalves de (2013)
The development of more selective and sensitive analytical methods is of great importance in different areas of knowledge, covering, for example, food, biotechnological, environmental and pharmaceutical sectors. The study aimed to employ the technique electroanalytical differential pulse voltammetry (DPV) as an innovative and promising alternative for identification and quantification of organic compounds. The organic compounds were investigated in this study oxalic acid (OA) and folic acid (FA). The electrochemical oxidation of oxalic acid has been extensively studied as a model reaction in the boundary between the organic and inorganic electrochemistry. Since the AF, an essential vitamin for cell multiplication in all tissues, which is essential for DNA synthesis. The AF has been investigated using analytical techniques, liquid chromatography and molecular absorption spectrophotometry. The results obtained during the experimental procedure indicated that the process of electrochemical oxidation of oxalic acid is strongly dependent on the nature of the anode material and the oxidation mechanism, which affects their detection. Efficient removal was observed in Ti/PbO2 anodes, graphite, BDD and Pt 90, 85, 80 and 78% respectively. It was also shown that the DPV employing glassy carbon electrode offers a fast, simple, reliable and economical way to determine the AO during the process of electrochemical oxidation. Furthermore, electroanalytical methods are more expensive than commonly used chromatographic analysis and other instrumental methods involving toxic reagents and higher cost. Compared with the classical method of titration and DPV could be a good fit, confidence intervals and detection limits confirming the applicability of electroanalytical technique for monitoring the degradation of oxalic acid. For the study of AF was investigated the electrocatalytic activity of the carbon paste electrode for identification and quantification in pharmaceutical formulations by applying the DPV. The results obtained during the experimental procedure showed an irreversible oxidation peak at 9.1 V characteristic of FA. The carbon paste sensor showed low detection limit of 5.683×10−8 mol L-1 reducing matrix effects. The spectrophotometric analysis showed lower concentrations of HF compared with those obtained by HPLC and DPV. The levels of AF were obtained according to the methodology proposed by the Brazilian Pharmacopoeia. The electroanalytical method (DPV) proposed is cheaper than GC analysis commonly used by the pharmaceutical industry. The results demonstrated the potential of these electroanalytical techniques for future applications in environmental, chemical and biological sensors